The Unintended Consequences of Cohorts: How Social Relationships Can Influence the Retention of Rural Teachers Recruited by Cohort-Based Alternative Pathway Programs - Daisy Rooks (Journal of Research in Rural Education, 2018)
To understand the social experiences of rural teachers recruited by cohort-based alternative pathway programs in the United States, I interviewed 17 rural teachers recruited by Teach For America (TFA). While many new rural teachers experience social isolation early in their careers when teaching in communities in which they did not grow up, these rural TFA teachers experienced very little social isolation. Instead, they were embedded in insulated but dense social networks comprised primarily of other TFA teachers. The richness of these teachers' social lives refl ects shared life stage, similar worldviews, and proximity, as well as TFA's institutional practices. The type and composition of their relationships appears to have infl uenced these teachers' short- and long-term retention in rural schools and communities. Personal relationships with short-time residents and utilitarian friendships with long-time rural residents appear to have promoted their short-term retention and undermined their long-term retention, while personal relationships with long-time rural residents appear to have promoted their short- as well as long-term retention, especially when they were romantic. To improve the longterm retention of participants, I conclude that cohort-based alternative pathway programs operating in rural schools and communities should deemphasize friendships with short-time residents, actively encourage personal friendships with longtime residents, and recruit long-time residents of the rural communities where they operate.